2018
DOI: 10.1038/gim.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 17 genes detects mutations in 81% of 811 patients with lissencephaly

Abstract: Purpose To estimate diagnostic yield and genotype-phenotype correlations in a cohort of 811 patients with lissencephaly or subcortical band heterotopia. Methods We collected DNA from 756 children with lissencephaly over 30 years. Many were tested for deletion 17p13.3 and mutations of LIS1, DCX and ARX, but few other genes. Among those tested, 216 remained unsolved and were tested by a targeted panel of 17 genes (ACTB, ACTG1, ARX, CRADD, DCX, LIS1, TUBA1A, TUBA8, TUBB2B, TUBB, TUBB3, TUBG1, KIF2A, KIF5C, DYNC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
131
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 35 publications
4
131
2
3
Order By: Relevance
“…In fact, for TUBA1A and TUBB2B alone, there are now 71 identified variants in cortical malformation patients (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(27)(28)(29)(30)(31)(32)(33)(34). Mutations of TUBA1A and TUBB2B account for ~5% and ~1.2% of lissencephaly and related malformations of cortical development (32). Both, but especially TUBA1A, are associated with a wide spectrum of severity (32).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, for TUBA1A and TUBB2B alone, there are now 71 identified variants in cortical malformation patients (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(27)(28)(29)(30)(31)(32)(33)(34). Mutations of TUBA1A and TUBB2B account for ~5% and ~1.2% of lissencephaly and related malformations of cortical development (32). Both, but especially TUBA1A, are associated with a wide spectrum of severity (32).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of TUBA1A and TUBB2B account for ~5% and ~1.2% of lissencephaly and related malformations of cortical development (32). Both, but especially TUBA1A, are associated with a wide spectrum of severity (32). With the exception of one variant inherited from a mosaic parent (6), all of these variants are heterozygous, de novo changes in the identified proband and not recessively inherited.…”
Section: Introductionmentioning
confidence: 99%
“…Although, it was initially suggested that LIS1 missense mutations may result in a less severe phenotype (Leventer et al, ), the increased number of reports have shown that the phenotypic spectrum actually spans from normal IQ to severe intellectual disability, and from mild MRI findings, such as posterior subcortical band heterotopia, to severe lissencephaly (Leventer et al, ; Saillour et al, ). Interestingly, a missense variant affecting the same residue as in our patients but resulting in a different amino acid change (c.655 T > G; p.Trp219Gly) has been reported in a wheelchair‐bound girl exhibiting severe developmental delay, drug‐resistant epilepsy since 8 months and pachygyria‐agyria with posterior predominant gradient (Di Donato et al, ). The striking difference in phenotype severity between our patients carrying the p.Trp219Arg variant and the reported girl with the p.Trp219Gly variant further confirms the extreme phenotypic variability associated with LIS1 missense mutations.…”
Section: Discussionmentioning
confidence: 51%
“…7,8 These observations can be supported by DYNC1H1-associated human disorders, which can give rise to a diverse array of autosomal-dominant neurological disorders including Charcot-Marie-Tooth (MIM: 614228), 9 spinal muscular atrophy (MIM: 158600), 10 intellectual disability (MIM:614563), 11,12 and lissencephaly. 13 Furthermore, copy number variation (CNV) deletions encompassing DYNC1I1 at 7q21.3 have been implicated in intellectual disability, developmental delay, and craniofacial dysmorphism with or without ectrodactyly, 14,15 although the precise gene driver for the neurological features has yet to be elucidated. The involvement of the dynein-1 molecular module in neurodevelopment is exemplified further by the observation that some dynein-1 complex genes, such as DYNC1I1 and DYNC1I2, have tightly regulated expression and undergo extensive alternative splicing to enable production of isoforms that are involved in discrete cargo specificity and binding tasks in neuronal tissues.…”
Section: Introductionmentioning
confidence: 99%